Kepemimpinan Kepala Sekolah Menengah Pertama (Studi Situs di SMP Muhammadiyah 9 Todanan-Blora) - Rahman, Handika (2015)
The aim of this research is to describe the principal to manage human resources, infrastructure and budget in SMP Muhammadiyah 9 Todanan. This research concentrate on the leadership style of the principal. The method used is qualitative method which concentrates on qualitative descriptive design. The principal has tasks to implement the functions of the leader, as the functions has relationship, with the aim of education and create good teaching and learning process effectively and efficiently. The principal must pay attention to the need and interest of infrastructure by involving the teacher. The job descriptions are needed nad he can appoint someone to manage the curriculum. So, the teaching and learning process can be maximized. The principal can focuse on coordination, communication, partnership with treasurer, school committee and parent. Keywords: leadhership, human resources, infrastructure, budget.